DIAGNOSIS OF THE CORROSION STATE OF HYDRAULIC STRUCTURES IN THE CASPIAN SEA IN ORDER TO PREVENT ENVIRONMENTAL DAMAGE - Mammedov K.A.,; Hamidova N.S.,; Ulkar Kamal Huseynova, (Scientific Journal of Pedagogy and Economics, 2020)
. In order to determine the corrosive state of offshore hydraulic structures subject to strong wave impacts, and to prevent environmental damage, the monitoring was carried out at “Oil Rocks” during 5 years. Surveys showed that on piles of overpass structures that have been in operation for 12-20 years, the corrosion rate is on average 0.22 mm / year. At the same time, at individual facilities, it ranges from 0.15 to 0.28 mm / year. The average loss of pile wall thickness is 32%, while at individual sites they range from 17 to 51%. The technology for the manufacture of structures of the surface complex should provide for high-quality factory deposition of corrosion-resistant coatings that provide at least 30 years of service without restoration. If the protective coating of the supports of hydraulic structures is destroyed during operation, it is proposed to use compositions based on cheap raw materials.